New and Rare Species of Orthocladiinae (Diptera, Chironomidae) from the Crimea, Ukraine - Baranov, V.A. (Вестник зоологии, 2011)
Parorthocladius korneyevi Baranov, sp. n. and Prosmittia valentinae Baranov, sp. n. from the Crimean Peninsula are described and illustrated. Three species of Orthocladiinae: Bryophaenocladius akiensis (Sasa, Shimomura et Matsuo, 1991), Corynoneura lacustris Edwards, 1924 and Metriocnemus eurynotus (Holmgren, 1883) are recorded for the first time from the Ukraine. Даны иллюстрированные описания Parorthocladius korneyevi Baranov, sp. n. и Prosmittia valentinae Baranov, sp. n. с Крымского полуострова. Три вида Orthocladiinae: Bryophaenocladius akiensis (Sasa, Shimomura et Matsuo, 1991), Corynoneura lacustris Edwards, 1924 и Metriocnemus eurynotus (Holmgren, 1883), – указаны впервые для фауны Украины.